2014
DOI: 10.12692/ijb/4.7.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total aqueous stem bark extract of spondias mombin l. on some biochemical and anthropometric parameters in wistar albino rats

Abstract: Spondias mombin L. (Anacardiaceae) is a medicinal plant used in the treatment of digestive disorders in Côte d'Ivoire. In order to verify its safety, the total aqueous stem bark extract is administered orally daily for 28 days, three groups of albino Wistar rats at 250, 500 and 1000 mg / kg body weight. The control group received distilled water. Measurements are made to determine the daily amount of food and the volume of water consumed, the body mass is evaluated each week. A blood sample is taken once a wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
0
1
2
Order By: Relevance
“…The decrease in the level of creatinine showed that a dose of 600 mg/kg of body weight of HAETM would not alter the proper functioning of the kidneys. However, our results differ from those of Gbogbo et al [31] who observed a significant difference in the increase of creatinine levels in rats treated with aqueous stem bark extract of Spondias mombin with a dose of 500 and 1000 mg/kg body weight compared to the spleen observed in the controls. They also noticed that the levels of creatinine and urea of treated rats remained lower compared to controls during the first three weeks of the study.…”
Section: Discussioncontrasting
confidence: 99%
“…The decrease in the level of creatinine showed that a dose of 600 mg/kg of body weight of HAETM would not alter the proper functioning of the kidneys. However, our results differ from those of Gbogbo et al [31] who observed a significant difference in the increase of creatinine levels in rats treated with aqueous stem bark extract of Spondias mombin with a dose of 500 and 1000 mg/kg body weight compared to the spleen observed in the controls. They also noticed that the levels of creatinine and urea of treated rats remained lower compared to controls during the first three weeks of the study.…”
Section: Discussioncontrasting
confidence: 99%
“…Koné et al (2009) ont également montré dans leurs travaux une absence de perturbation sur quelques marqueurs biochimiques hépatiques après administration d'un phytomédicament chez des rats Wistar albinos sur une période de 28 jours aux doses de 3,5 ; 35 et 350 mg/kg de poids corporel. Ces résultats diffèrent cependant de ceux obtenus par Gbogbo et al (2014). Ces derniers ont montré que l'administration subaiguë de l'extrait total aqueux des écorces de tige de spondias mombin L. entraînerait une augmentation graduelle des marqueurs hépatiques au cours du traitement.…”
Section: Discussionunclassified
“…Selon Ariarajah et al (2011) la créatinine est le paramètre d'exploration rénale le plus utilisé et son augmentation sérique peut être expliquée par une atteinte de la fonction rénale. D'autres auteurs ont également montré l'effet toxique de certains phytomédicaments sur la fonction rénale par l'augmentation du taux sérique de la créatinine (Ashraf et al, 2013 ;Gbogbo et al, 2014 ;Awotundea et al, 2019). Hormis la créatinine, les autres paramètres n'ont pas connu de perturbations notables au cours de l'étude.…”
Section: Discussionunclassified